Paysage scriptural adolescent, du papier au numérique - Elisabeth Schneider (Recherches en Éducation)
These methodological considerations are part of a thesis on the writing practices of teenagers and their spatial organization of what we choose to call “a complex scriptural landscape”. The complexity and the richness of these spatial practices refer to the question of the production of a social reality that we try to question as a geographical problem and as matter concerning the information and communication sciences. Therefore, the writing of teenagers is studied as a tool to produce social spaces and to afford self-mediation and the development of their identity. Drawing on an ethnographical survey, we try to study both the methodological aspect and the epistemological one, which are jointly builded.